Testing of Force Sensors for the Active Measurement and Limitation of Axial Loads in Heavy Turning - Marcin Kasprzak; Michał Pyzalski (Journal of Machine Engineering)
This article describes the design and construction of a feed drive load measuring system based on industrial strain gauges installed in the machine tool structure. The system was calibrated and dynamically tested in the range of 15kN in real machining conditions. The tests showed that the system installed on a machine tool works correctly and its error amounts to about 5% of the measured range. Thanks to this measuring system the accuracy of the machine tool in machining conditions can be increased through the active compensation of the axial error caused by displacements. Moreover, the system can prevent tool breakage and increase machining efficiency.